POSTPRANDIAL VARIATIONS IN BLOOD PRESSURE IN THE ELDERLY PEOPLE - Yusuf, Muhammad; Badar, Ahmed; Ansari, Ahmad Kamal (Journal of Ayub Medical College Abbottabad, 1990)
ABSTRACT Ageing is associated with changes and deterioration in functions and structure of many systems including cardiovascular system. Besides other changes the activity of baroreceptors and autonomic system, both of which are important for the homeostasis of blood pressure under different physiological conditions in daily life, is said to be reduced with the advancing age. Food intake is one of the important factors, which influence the cardiovascular system, and readjustments take place in the system for blood pressure homeostasis after ingestion of meal. The present study was planned to evaluate and compare the postprandial changes in blood pressure in young adults and elderly people. A total of 70 male healthy individuals (50 elderly & 20 young adults) were selected for the study. Blood pressure and pulse rate were measured before a standard breakfast and then at intervals of 15 minutes each, after meal, for one hour. In the young adults group, the systolic, diastolic and mean arterial pressure showed no significant change after meal while pulse pressure was raised for first 30 minutes after meal, returning again to almost pre-prandial level in next 30 minutes. The pulse rate was however increased significantly after meal. In the elderly subjects, on the other hand, there was moderate to marked decline in systolic, diastolic, mean arterial and pulse pressures without any increase in the pulse rate. This response to meal in the elderly subjects was found to be significantly different from that in the young adults.